Otimização do processo de imobilização de Beta - galactosidase de Aspergillus oryzae em alginato de sódio com gelatina e glutaraldeído - Freitas, Fernanda Ferreira (2007)
In this work was studied the simultaneous influence of sodium alginate, gelatin and glutaraldehyde concentrations in the immobilization process of Beta-galactosidase from Aspergillus oryzae and the kinetic of lactose hydrolysis by the enzyme in the soluble and immobilized forms. The free enzyme was studied at 35°C and in a pH of 4.5, showing that for substrate concentrations up to 90g/L, the Michaelis-Menten model fitted the experimental data, with a Km and Vm value of 17.83 g/L (52.13 mM) and 1032.07 gglicose/L.min.mg proteína respectively. Galactose acted as a competitive inhibitor on the free enzyme kinetic, presenting kinect constants Ki and Km values of a 1.015 and e 17.61 g/L respectively. The enzyme was stable at pH values ranging from 4.5 to 7.0 and a maximum temperature activity of 55°C, with an activation energy of 6.9 kcal/mol. The thermal stability of the enzyme was studied from 53 to 65°C, presenting a half-life of 7.7 hours at 53°C. The activation energy for the thermal deactivation process was 88.14 kcal/mol. Through a central composite design, the sodium alginate, gelatin and glutaraldehyde concentrations that maximized the -galactosidase from Aspergillus oryzae activity in the inhibition process were, respectively, 6.60%(w/v), 4.05%(w/v) and 3.64%(v/v). The immobilized enzyme presented a 20% drop in activity after 25 uses. The immobilization yield found was 30%. The enzymatic activity for the immobilized form was maximum at pH of 5.0 and 60°C, determined through a central composite design. The reaction activation energy for the immobilized enzyme was 7.74 kcal/mol. The immobilized biocatalyst was stable on pH values ranging from 4.5 to 7.0. The half-life time of the immobilized enzyme was 12.8 hours at 53°C, with a activation energy for the thermal deactivation process value of 72.03 kcal/mol . The substrate concentration influence was studied from 5 to 140 g/L of lactose and the Michaelis-Menten model fitted the experimental data, with Vm and Km values of 1428.14 glactose/min.m3catalyst and 20.62 g/L (60.3 mM), respectively. It was observed a small resistance to lactose mass transfer at the biocatalyst particles, in the immobilized enzyme, due to the high effectiveness factor values. The inhibition model fitted the experimental data and the adjusted Km and Ki values were 16.7 and 9.6g/L, respectively.